2020
DOI: 10.1101/2020.06.02.130930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Basis of Far-red Sensing in Cyanobacteriochrome

Abstract: Author contributionsXY designed the project; SB, SSM and XZ carried out cloning, purification, and crystallization; SB, XZ, SSM and NR conducted mutagenesis and spectroscopic experiments; SB, XZ, ZR, HS and XY collected monochromatic diffraction data; HS, CW and ZR collected Laue diffraction data; ZR processed the Laue data and carried out singlecrystal spectroscopic experiments; SB and XY determined, refined and analyzed crystal structures; NR carried out phylogenetic analysis; SB, XY, NR, MVM, and JCL interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…The first system is a novel far-red photoreceptor that confers reversible photoconversion between the far-redabsorbing (Pfr) state and orange-absorbing (Po) state based on a single bilin-binding GAF domain (Bandara et al, 2020). Since our photoreceptor construct corresponds to the third GAF domain of a multi-domain sensory histidine kinase from Anabaena cylindrica PCC 7122, we refer to this crystal as G3 hereafter.…”
Section: Serial Laue Datasets Of Bilin-based Photoreceptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first system is a novel far-red photoreceptor that confers reversible photoconversion between the far-redabsorbing (Pfr) state and orange-absorbing (Po) state based on a single bilin-binding GAF domain (Bandara et al, 2020). Since our photoreceptor construct corresponds to the third GAF domain of a multi-domain sensory histidine kinase from Anabaena cylindrica PCC 7122, we refer to this crystal as G3 hereafter.…”
Section: Serial Laue Datasets Of Bilin-based Photoreceptorsmentioning
confidence: 99%
“…which are as photoactive as in solution (Bandara et al, 2020). Using conventional cryocrystallography, we obtain crystallography datasets of G3 in the space group P4 2 22 up to 2.9 Å resolution.…”
Section: Serial Laue Datasets Of Bilin-based Photoreceptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The red/green subfamily harbors a fully protonated chromophore in both photostates, but a twisted conformation of the A-and Drings is responsible for the blue-shifted photoproduct (8,(20)(21)(22)(23); this is known as the "trappedtwist photocycle" (24). Recently, Bandara et al reported the structure of a far-red absorbing state of a CBCR that adopts a atypical C15-Z,syn configuration (25). They proposed a model that its far-red absorption maximum arises from a cationic bilin tautomer in which the A-ring is formally di-protonated while the B-ring remains deprotonated.…”
Section: Introductionmentioning
confidence: 99%